A Review of Simulation Urban Growth Model - Nugroho, Feri; Ismael Al-Sanjary, Omar; ., . (International Journal of Engineering and Technology, 2018)
Urban development has become a problem in many cities, especially in developing countries. The availability of areas for development is needed to deal with rapid population growth and urbanization. The purpose of this study was to identify urban growth models. Due to urban growth planning, the city will be more manageable and organized. From the conclusions of urban modeling identification can provide an idea of what model is appropriate for use in urban growth studies. The results of this urban growth model identification could be a reference in urban growth modeling in better urban planning.Â Â